The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/ijlm-12-2020-0465
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supply chain relationship configurations on supplier performance: investigating buyer–supplier relations in the aerospace industry

Abstract: Purpose A supplier may sell not only to one buyer (sole relationship configuration) but also to the buyers competitors (shared relationship configuration) for a specific product category. This study examines the performance implications when suppliers establish shared relationships with the buyer’s competitors.Design/methodology/approach Secondary data are used to test hypotheses relating a supplier’s relationship configurations to its operational performance. A seemingly unrelated regression approach (SUR) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
(230 reference statements)
0
7
0
1
Order By: Relevance
“…This involves setting ambitious emission reduction targets, identifying areas where emissions can be reduced and investing in the development and deployment of new technologies that can reduce emissions (Frank et al, 2021). Another implication is the need to collaborate with industry stakeholders, such as airports, manufacturers and fuel suppliers, to develop sustainable ecosystems (Paleari, 2022;Schmelzle and Mukandwal, 2023). Governments can provide support by funding research and development of sustainable aviation technologies, providing incentives for operators to adopt sustainable practices and implementing policies that promote the use of sustainable fuels (Bullerdiek et al, 2021;Santos and Delina, 2021).…”
Section: Climate-neutral Transportationmentioning
confidence: 99%
“…This involves setting ambitious emission reduction targets, identifying areas where emissions can be reduced and investing in the development and deployment of new technologies that can reduce emissions (Frank et al, 2021). Another implication is the need to collaborate with industry stakeholders, such as airports, manufacturers and fuel suppliers, to develop sustainable ecosystems (Paleari, 2022;Schmelzle and Mukandwal, 2023). Governments can provide support by funding research and development of sustainable aviation technologies, providing incentives for operators to adopt sustainable practices and implementing policies that promote the use of sustainable fuels (Bullerdiek et al, 2021;Santos and Delina, 2021).…”
Section: Climate-neutral Transportationmentioning
confidence: 99%
“…The two market CSFs comprise integration and external assistance. An interactive supply chain is characterised by stringent stakeholder expectations, robust supplier relationships, and extensive information sharing within the supply chains (Duong et al ., 2023; Schmelzle and Mukandwal, 2022; Kirezieva et al ., 2015b). Improved quality, lower costs, and consistent delivery are the competitive advantages primarily driven by the greater integration between multiple stakeholders in the food supply chain (Nguyen and Li, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Liberopoulos and Deligiannis [39] developed an optimal inventory control policy for a supplier when the buyer's purchase decision is influenced by past service levels, which considers the buyer's ordering behavior and the supplier's capacity constraints and trade credit terms, and they showed that the optimal policy can achieve substantial cost savings for both parties. Schmelzle and Mukandwal [40] investigated the impact of supply chain relationship configurations on supplier performance by analyzing buyer-supplier relationships in the aerospace industry, which identified the key dimensions of relationship quality, including trust, communication, and coordination, and they showed that high-quality relationships lead to improved supplier performance in terms of cost, quality, and delivery. Ventura et al [41] studied a multi-period dynamic supplier selection and inventory lot-sizing problem with multiple products in a serial supply chain which incorporated a richer cost structure involving joint replenishment costs for raw material replenishment and production, and an accurate representation of the transportation costs using a vector of full-truck load costs for different size trucks.…”
Section: Supplier Selectionmentioning
confidence: 99%
“…When the production rates of suppliers are greater than or equal to the demand rate, Equations ( 8) and ( 9) can be rewritten as Equations (39) and (40) to represent suppliers' inventory, I S k , k∈ R 1 , and inventory holding cost (IHC S R 1 ), as shown in [1].…”
Section: Condition 1 (P K ≥ D)mentioning
confidence: 99%